2010
DOI: 10.5194/bgd-7-2927-2010
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effect of ocean acidification on the early life stages of the blue mussel (<I>Mytilus edulis</I>)

Abstract: Several experiments have shown a decrease of growth and calcification of organisms at decreased pH levels but relatively few studies have focused on early life stages which are believed to be more sensitive to environmental disturbances such as hypercapnia. Here, we present experimental data demonstrating that the growth of planktonic mussel (Mytilus edulis) larvae is significantly affected by a decrease of pH to a level expected for the end of the century. Even though there was no significant effect of… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
76
2
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(89 citation statements)
references
References 29 publications
9
76
2
2
Order By: Relevance
“…More sensitive early life-history stages of M. edulis from the Skagerrak have been shown to respond differently to ocean acidification: fertilization success increased at reduced pH (induced by high pCO 2 ) whereas subsequent larval shell growth was negatively affected, albeit only slightly (Renborg and Havenhand, unpublished results). Similar small negative effects on larval shell growth have also been reported in populations of M. edulis from the North Sea (Gazeau et al 2010;Bechmann et al 2011), and in related Mytilus species around the world (Kurihara et al 2009;Gaylord et al 2011;Sunday et al 2011). Early reports of the effects of ocean acidification on shell growth in adult M. edulis showed negative impacts (Gazeau et al 2007), a result that contrasts with those of Melzner and co-workers in the Kiel fjord (Thomsen et al 2010;Melzner et al 2011), although the latter might be expected to be a result of local adaptation to seasonally low pH-especially at such extreme levels (Melzner et al 2009b;Thomsen et al 2010).…”
Section: Macrozoobenthossupporting
confidence: 81%
“…More sensitive early life-history stages of M. edulis from the Skagerrak have been shown to respond differently to ocean acidification: fertilization success increased at reduced pH (induced by high pCO 2 ) whereas subsequent larval shell growth was negatively affected, albeit only slightly (Renborg and Havenhand, unpublished results). Similar small negative effects on larval shell growth have also been reported in populations of M. edulis from the North Sea (Gazeau et al 2010;Bechmann et al 2011), and in related Mytilus species around the world (Kurihara et al 2009;Gaylord et al 2011;Sunday et al 2011). Early reports of the effects of ocean acidification on shell growth in adult M. edulis showed negative impacts (Gazeau et al 2007), a result that contrasts with those of Melzner and co-workers in the Kiel fjord (Thomsen et al 2010;Melzner et al 2011), although the latter might be expected to be a result of local adaptation to seasonally low pH-especially at such extreme levels (Melzner et al 2009b;Thomsen et al 2010).…”
Section: Macrozoobenthossupporting
confidence: 81%
“…Following this time, the mussels developed shell abnormalities including protrusions of the mantle and convex hinge, reductions in both shell height and length as well as an increase in development time. Similar results were found in the mussels M. edulis (Gazeau et al 2010) and M. trossulus , where larvae …”
Section: Kimura Et Al (2011)supporting
confidence: 75%
“…Up and down regulation of genes associated with various pathways during exposure to ocean acidification suggests an organisms effort to compensate for the effects of elevated pCO 2 [81]. There have also been studies which highlight the variability in the potential ecotoxicological consequences associated with elevated CO 2 accumulation of metals varied; 110m Ag increased and 109 Cd decreased with decreasing pH, whereas 65 Zn accumulation was highest at pH 7.85, but lower at pH 7.6 than 8.1 (control, [71]) in the cuttlefish Sepia officinalis.…”
Section: Mechanisms In Echinoderms and Molluscsmentioning
confidence: 99%
“…A number of studies have found a delay in development or less development (the oysters Crassostrea gigas and Saccostrea glomerata [33,35,39]; the mussel M. galloprovincialis [57]; gastropod Littorina obtusata [63]), morphological shell abnormalities such as convex hinge and mantle protrusion and impacts on calcification size and growth rate (the oyster Crassostrea gigas [33,35,39]; the mussel M. galloprovincialis [57]; gastropod, Littorina obtusata shorter lateral, but longer spiral shell length [63] and Saccostrea glomerata [35,39,64]), decreases in shell length and thickness in the mussel (Mytilus edulis [65]), hatching rate (gastropod, Littorina obtusata [63], mussel Mytilus edulis [65]), degraded shells (mussel Mytilus edulis [65], polar pteropod Limacina helicina [66]) decreased rate of metamorphosis, shell thickness and loss of hinge integrity (bay scallop Argopecten irradians and the hard clam Mercenaria mercenaria [67]) and in the Mediterranean pteropod Cavolinia inflexa [68] shells were absent after 13 days due to dissolution, yet larvae displayed "normal" swimming action (Table S2). In rare instances there have been positive instead of negative impacts of elevated CO 2 .…”
Section: Molluscsmentioning
confidence: 99%